A study of squeal noise in a disc brake system and influence of rubber coated shims on system damping - Balvedi, Alessandro Mattiuzi (2002)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico. Programa de Pós-Graduação em Engenharia Mecânica.